The Influence of Educational Management, Community Participation, and Financial Supervisin on Education Quality - Rinny Hariyanti; Maryanto; Ghufron Abdullah (Prodi Pendidikan Agama Islam FTIK IAIN Palopo, 2024)
This study investigates the impact of educational fund management, community participation, and financial supervision on the quality of education in public junior high schools (SMP Negeri) in Cepu District. Using a quantitative approach with a correlational method, the study involved 191 teachers, with 129 selected as samples through stratified random sampling. Data were collected via questionnaires and analyzed using descriptive statistics, assumption tests, and regression analysis. The findings show that: (1) educational fund management positively influences education quality by 10.1%, (2) community participation has a positive impact of 22.7%, (3) financial supervision affects education quality by 23.7%, and (4) all three factors together contribute 34.3% to education quality. The study concludes that improving education quality requires effective fund management, enhanced community participation, and transparent financial supervision. Keywords: Education quality; educational fund management; community participation; financial supervision